Plasticity of the gut microbiome of golden snub-nosed monkeys (Rhinopithecus roxellana) in response to seasonal variation in diet - Mingyi Zhang; Xiaochen Wang; Hui Yao; Ying Shen; Yang Teng; Paul A. Garber; Huijuan Pan; Ming Li (npj Biofilms and Microbiomes)
Abstract The effects of seasonal fluctuations in food availability on gut microbiome composition, diversity, and function present significant challenges to animals with hard-to-digest diets. Here, we investigate seasonal variation the gut microbiome of wild golden snub-nosed monkeys (Rhinopithecus roxellana), a foregut fermenting primate, using metagenomics and metatranscriptomics data. We reconstructed 578 metagenome-assembled genomes (MAGs), 76.5% of which did not have exact matches in reference databases, highlighting the novelty of their gut microbiota. The gut microbiome of wild golden snub-nosed monkeys exhibited high diversity and enrichment in plant secondary compound metabolism during summer, while in winter it was enriched with enzymes that function in lichen polysaccharide degradation and Lachnospiraceae, which is important for energy balance. Captive monkeys on a consistent diet showed minimal seasonal variation in gut microbiome composition. Habitat changes also affected golden snub-nosed monkey microbiota community assembly and carbon cycling pathways. These findings underscore the gut microbiome’s plasticity in meeting host dietary needs under varying environmental conditions.